A social network analysis of interconnections among cruise ports - Uriel Armando Lopez Rodriguez; Sung-Hoon Park; Dong-Myung Kim; Gi-Tae Yeo (Asian Journal of Shipping and Logistics (AJSL), 2021)
Despite the dominance of the Caribbean as the leading cruise destination in the world, research that focuses on the network of cruise ports in the region is limited. To fill this research gap, the current study carried out social network analysis (SNA) to inquire into cruise port interconnections and their influence on the operation of the entire Caribbean port network. The results are summarized as follows: First, in terms of connections among ports linked to the Caribbean region, a European port and a Southampton harbor exhibit the most significant in-degree and out-degree centrality. Nevertheless, ports within the Caribbean region are still significantly represented as regards both indexes. Second, in the matter of port influence, Caribbean ports are considerably the most important with respect to hub and authority centrality (HAC), especially those located in Florida and the eastern Caribbean. This research contributes to industry through its presentation of an extended panorama of the cruise network in the region, subjecting several ports to respective analyses that describe their principal characteristics and attractiveness in the industry.
Keywords: 650; Caribbean; Connection; Cruise port; Hub and authority centrality (HAC); Port network; Social network analysis (SNA)